SAT0628-HPR "IT IS THE NEVER ENDING QUEST, HOW TO MOTIVATE PEOPLE" – HEALTH PROFESSIONALS' PERSPECTIVES ON SUPPORTING PHYSICAL ACTIVITY MAINTENANCE IN THOSE LIVING WITH AXIAL SPONDYLOARTHRITIS. (2nd June 2020) - Ingram, T.; Rouse, P.; Standage, M.; Sengupta, R.
Abstract : Background: Physical activity (PA) has been identified as a primary treatment option for people living with axial spondyloarthritis (axSpA) [1]. Yet, people living with axSpA can find it difficult to maintain PA at levels required to gain the evidenced benefits [2]. Intensive rehabilitation programmes harness the benefits of physical activity, but little is known about how to support PA maintenance when patients return to everyday life. The perspectives' of health professionals involved in rehabilitation programmes can provide important and rich insights into how people living with axSpA could be helped to maintain their PA. Objectives: To explore health professionals' experiences of supporting PA maintenance during and after a rehabilitation programme for those living with axial spondyloarthritis. Methods: A qualitative study was conducted using semi-structured interviews. Nine health professionals (i.e., 4 physiotherapists; 1 clinical nurse specialist; 1 rheumatology SpR; 1 psychologist; 1 occupational therapist; and 1 podiatrist) who contribute to a rehabilitation programme were recruited from the Royal National Hospital for Rheumatic Diseases in Bath, UK ( M time contributing to course = 6.79 yrs, range 1-19.25 yrs; contact time over course range = 1 to 45 hrs). Interviews were audio recorded, transcribed verbatim, and a thematic analysis employed [3]. Results: Maintaining a physically active lifestyle is a challenge for those living with axSpA and is an issue that is currently not being addressed. Health professionals' perspectives on supporting PA maintenance was illustrated through four main themes: (1) Social environment (group dynamic, importance of others with the same condition, immersion of the disease, external peer groups); (2) Re-framing (education, ownership, exercise off the pedestal, combating fear, routine and habit); (3) PA support (enjoyment and interest, PA as flexible, encouragement and importance, balance and realistic expectations, internal and external feedback); and (4) Challenges for health professionals (training, resources, knowledge of transition process to everyday life, difficulty motivating). The reasons why people engage in PA play a key role within each of these themes. Conclusion: Results emphasize the current lack of support for the maintenance of PA and the complexities and challenges involved in maintaining PA for people living with axSpA. Interventions to support PA maintenance should pay particular attention to the importance of socially supportive environments, the need for enjoyment, and the use of internal and external feedback. The challenges faced by health professionals in motivating those living with axSpA to engage in PA regularly suggests a need for more training opportunities in motivation and health behaviour change. References: [1]Rausch Osthoff, A., Niedermann, K., Braun, J., et al., (2012) EULAR recommendations for physical activity in people with inflammatory arthritis and osteoarthritis . Annals of the Rheumatic Diseases, 77 (9), pp. 1251-60. [2]McDonald, M. T., Siebert, S., Coulter, E. H., McDonald, D. A., and Paul, L. (2019) Level of adherence to prescribed exercise in spondyloarthritis and factors affecting this adherence: a systematic review. Rheumatology International, 39 (2), pp. 187-201. [3]Braun, V., and Clarke, V. (2006) Using thematic analysis in psychology. Qualitative Research in Psychology, 3 (2), pp. 77-101. Acknowledgments: The authors would like to thank the Bath Institute for Rheumatic Diseases (BIRD) and the University of Bath for funding the PhD studentship associated with this project Disclosure of Interests: Thomas Ingram: None declared, Peter Rouse: None declared, Martyn Standage: None declared, Raj Sengupta Grant/research support from: Research grants from UCB, Pfizer, Abbvie and Novartis, Speakers bureau: Received honoraria for giving talks from Abbvie, Biogen, UCB, Novartis, Pfizer